(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
Pedagogical games in preschool organizations are characterized by the style of play as follows: by topic; photo; business, imitation, dramatic games. All pedagogical games used in the system of higher, secondary special, vocational education are, in essence, business games. Because they are usually developed within a specific learning discipline: there are roles and plots, different situations are imitated. That is, business games used in the system of higher and secondary special vocational education include all components of pedagogical games